Hematological and Biochemical evaluation after different orally doses of Copper sulfate in rats: Rajiha A. Al- Naimi ; Nibras H.Al-Tayar; Layth A.M. Alsoufi and Eman H.Y.Al-Taae - Al- Naimi, Rajiha A. (The Iraqi Journal of Veterinary Medicine, 2014)
Objectives of this study were to evaluate hematological and biochemical parameters in rats ingested toxic doses of CuSO4.5H2O. Thirty six rats divided into 3 equal groups. First group ingested orally distilled water / day for 3 months and considered as control group , second group was drenched 8 mg /kg B.W /day of CuSO4.5H2O for 3 months and considered as Treated group1 (T1). Third group was drenched 40 mg /kg B.W /day of CuSO4.5H2O for 3 months and considered as Treated group2 (T2). Blood collection was done by direct cardiac puncture every month for hematological and biochemical examinations. Hematological parameters showed that anemia caused by CuSO4.5H2O toxicity was of microcytic hypochromic type with significant increase of neutrophils and decrease of lymphocytes and blood platelets. There was significant increase in biochemical parameters , liver enzymes (GOT,GPT,ALP) and total serum protein . It concluded that CuSO4.5H2O poisoning in rats causes significant changes in blood picture and clinical enzyme